2010
DOI: 10.2460/ajvr.71.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the analgesic effect of intracameral lidocaine hydrochloride injection on intraoperative and postoperative pain in healthy dogs undergoing phacoemulsification

Abstract: Intracameral lidocaine injection had significant analgesic effects in dogs undergoing cataract surgery. Results of this study suggest the value of intracameral lidocaine injection as an analgesic for intraocular surgery in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
1
19
0
2
Order By: Relevance
“…An additional limitation of this study is that pain assessment in animals is highly subjective and response to pain among animals is variable. This was demonstrated by the unexpectedly low 50% rescue rate noted in the control group of this study as well as in other canine pain studies 47,48 . Multiple studies demonstrate that even with appropriate scoring systems, control groups may not always have a 100% rescue rate 34,47,48 .…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…An additional limitation of this study is that pain assessment in animals is highly subjective and response to pain among animals is variable. This was demonstrated by the unexpectedly low 50% rescue rate noted in the control group of this study as well as in other canine pain studies 47,48 . Multiple studies demonstrate that even with appropriate scoring systems, control groups may not always have a 100% rescue rate 34,47,48 .…”
Section: Discussionsupporting
confidence: 46%
“…This was demonstrated by the unexpectedly low 50% rescue rate noted in the control group of this study as well as in other canine pain studies 47,48 . Multiple studies demonstrate that even with appropriate scoring systems, control groups may not always have a 100% rescue rate 34,47,48 . The pain scoring system used in this study was modified from the University of Melbourne Pain Scale 49 and has been validated in several previous studies, including ocular models, where control animals were rescued at significantly higher rates than other groups 48,50,51 .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, the HR and MAP did not alter significantly with time and were within the physiological range for cats in all treatment groups . Similarly, intracameral injection of lidocaine and epinephrine did not alter cardiovascular parameter in dogs, and humans …”
Section: Discussionmentioning
confidence: 74%
“…In addition, there are reports showing that intracameral lidocaine is able to decrease intraoperative pain and humans with high myopia submitted to phacoemulsification. Similar results showed that intracameral lidocaine injection reduced the intraoperative isoflurane concentration and additional postoperative analgesic requirements in dogs undergoing phacoemulsification …”
Section: Introductionmentioning
confidence: 99%